Virtual Reference Services in a Caribbean Academic Library: Helping Users Serve Themselves. Issue 1 (2nd January 2016) - Montalvo, Marilyn
ABSTRACT: This article describes acquiring a structured platform for collecting statistics and developing a thorough FAQ. The number of views received by the knowledge base reveals the usefulness of a tool which can help libraries provide accurate answers in a timely manner and within a cooperative environment.